2018
DOI: 10.18203/2320-6012.ijrms20181429
|View full text |Cite
|
Sign up to set email alerts
|

The study of clinical and endoscopic spectrum of upper gastrointestinal manifestations in HIV patients

Abstract: Background: Opportunistic disorders are the most frequent GI complications of HIV infection and remain a major cause of morbidity and mortality in these patients. These disorders account for high prevalence of upper gastrointestinal symptoms such as dysphagia, odynophagia, retrosternal chest pain, abdominal pain and upper GI bleeding. Hence an attempt is being made to study clinical, endoscopic and biopsy changes in HIV patients with upper GI symptoms which helps us to make early diagnosis of upper GI disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Other studies have reported diverse presenting complaints among the patients who reported for UGI endoscopy. The most common symptom encountered by Parashar and colleagues 12 , was epigastric pain seen in 49 (92.5%) patients followed by anorexia and weight loss in 45 (84.9%), and 41 (77.4%) patients respectively in an Indian hospital. Gado et al 9 , observed dyspepsia 1400 (31%), UGI bleeding 1155 (26%), and banding or sclerotherapy of varices 897 (20%) as the most frequent indications for UGI endoscopy in an Egyptian institute.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies have reported diverse presenting complaints among the patients who reported for UGI endoscopy. The most common symptom encountered by Parashar and colleagues 12 , was epigastric pain seen in 49 (92.5%) patients followed by anorexia and weight loss in 45 (84.9%), and 41 (77.4%) patients respectively in an Indian hospital. Gado et al 9 , observed dyspepsia 1400 (31%), UGI bleeding 1155 (26%), and banding or sclerotherapy of varices 897 (20%) as the most frequent indications for UGI endoscopy in an Egyptian institute.…”
Section: Discussionmentioning
confidence: 90%
“…Mahmood et al 14 , reported gastritis 106 (13.85%), esophagitis 85 (11.1%), duodenal ulcer 62 (8.1%), and hiatal hernia 55 (7.2%) as the common findings. Parashar and colleagues 12 , foundantral gastritis 14 (26.4%) followed by Candidal esophagitis 12 (22.6%) as the common findings. Gado et al 9 , observed the commonest significant pathologies being pepticulcer, esophagitis, and erosive gastroduodenitis, which were diagnosed in 18%, 14%, and 8% of the patients.…”
Section: Discussionmentioning
confidence: 94%